Health first, convenience second: Caregiver perspectives of commercially produced complementary foods in five Southeast Asian capital cities - Helen Walls; Alissa Pries; Saipin Chotivichien; Phuong Huynh; Umi Fahmida; Jessica Blankenship (Maternal and Child Nutrition, 2023)
Abstract Caregivers in low‐ and middle‐income countries increasingly feed commercially produced complementary foods (CPCF) to older infants and young children—shaped by factors including industry promotion. The dynamics of CPCF consumption and caregiver knowledge, attitudes and behaviours regarding complementary feeding practices are poorly understood in these settings. We examined how caregiver knowledge/attitudes/behaviours about CPCF shape the feeding of older infants and young children in the capital cities of five countries in Southeast Asia (Bangkok, Hanoi, Jakarta, Kuala Lumpur, Manila). An online, web‐based, cross‐sectional panel survey was conducted among mothers of a child aged 6−23 months. One hundred participants were included in each of the five capital cities. Questionnaires were undertaken in the official language of each city. Data were analysed in Stata (version 17.0), using χ2 tests to examine difference between variables of interest. All mothers purchased CPCF for their youngest child aged 6−23 months at the time of survey. CPCF were commonly fed to children at least once per day, and in many of the five cities at most or every feeding. While factors such as convenience and affordability influenced CPCF purchase, mothers primarily purchased CPCF for nutritional reasons. The most common source of feeding information was health care professionals, followed by social media. CPCF are ubiquitous in the diets of older infants and young children of educated middle–upper socioeconomic status mothers in capital cities of Southeast Asia, with perceived healthiness a key driver in selecting CPCF. A strong governmental regulatory response to industry marketing/promotion will be critical to addressing CPCF appropriateness, including health and nutritional claim use.